Enhanced Ultrasonography Using a Nano/Microbubble Contrast Agent for Islet Transplantation. Issue 6 (2nd April 2015) - Sakata, N.; Sax, N.; Yoshimatsu, G.; Tsuchiya, H.; Kato, S.; Aoki, T.; Ishida, M.; Katayose, Y.; Egawa, S.; Kodama, T.; Unno, M.
<x xml:space="preserve">Abstract</x> Recent basic and clinical studies have assessed the use of highly sensitive imaging modalities for visualizing transplanted islets. We investigated the utility of enhanced ultrasonography, combined with fluorescent acoustic liposome nano/microbubbles (FALs), for evaluating angiogenesis and the endocrine function of transplanted islets. BALB/c mice were classified into three groups: Diabetic mice that underwent syngeneic islet transplantation into the subrenal capsule and achieved normoglycemia (Tx group); those that failed to achieve normoglycemia (Tx‐DM group); and those not receiving any treatment (DM group). Mice were examined by FAL‐enhanced high frequency ultrasonography. The echogenicity of the islets increased rapidly within the first minute after injection of FALs and remained at a higher level in the Tx group, while small increases were observed in the other two groups. In histological assessments, fluorescently stained erythrocytes could be seen in and around the transplanted islets, indicating that the transplanted islets were enhanced by infusion of FALs via vessel networks between the engrafted islets and tissue. Furthermore, the echogenicity correlated significantly with endocrine parameters, including blood glucose (BG), serum insulin, and the BG change in the glucose tolerance test. In conclusion, the echogenicity of the islets under FAS‐enhanced ultrasonosonography correlated with the endocrine status of transplanted islets.